Posted by **ally** on Wednesday, February 20, 2013 at 6:52pm.

6∑6(2^K-1) K=1

## Answer this Question

## Related Questions

- statistics - I'm trying to work through the proof for SST = SSM + SSE MEAN = &#...
- Math - ∑(x+y) c. ∑(x+∑(y)) d. ∑x+ ∑y e. ∑(x...
- Calculus - Find a series ∑a_n for which ∑(a_n)^2 converges but &#...
- Math - Mathematical Induction - 3. Prove by induction that∑_(r=1)^n▒...
- Calculus - If a_n >0 and b_n >0 and series ∑ sqrt( (a_n)^2 +(b_n)^2...
- Statistics - 3. The formula for finding sample standard deviation is ...
- Calculus - If a_n does not equal zero for any n>=1 and ∑a_n converges ...
- calculus - Given that ∑(n=1 to inf) 1/(n^2) = (pi^2)/6, find the value of...
- math - Use the method of differences to prove the following formulas 1) ∑_...
- physics - Let |α⟩=1M√∑M−1j=0αj|j⟩ and ...